Impact of endovascular pedal arteries revascularization on wound healing in patients with critical limb ischemia - El Yamany, Mohamed M.; Mohamed, Hatem M.; Boulos, Meera R.; Raffat, Sherif A. (International Surgery Journal, 2020)
Background: Critical limb ischemia (CLI) is the final consequence of peripheral arterial disease (PAD). The management of this complex patient population often warrants a multidisciplinary approach with collaboration between endovascular interventionist, vascular surgeons, podiatrist, infectious disease, and wound care specialist. Objective of the study was to evaluate the impact of endovascular pedal arteries revascularization on wound healing in patients with critical limb ischemia. Methods: This was an interventional study conducted on 30 consecutive CLI patients underwent infra-genicular endovascular revascularization who attended to the outpatient department and emergency, Suez Canal university hospital complaining of symptoms of critical lower limb ischemia involving the foot (rest pain, ulcer and gangrene), during the period study from June 2017 till January 2019. Full detailed history, full examination, lab investigation, radiological imaging was done. Results: The pain intensity decreased from 7 to 4 post-procedural at 2nd day post-op, then to 3 at one week follow up and then it totally disappeared at one month follow up visit. The remaining patients who had incomplete PAA reported faster relieve of pain and more dramatic improve over time as it was totally relieved post procedural by time of discharge. The overall mean time required to achieve wound healing was 15±8 weeks. Conclusion: Successful pedal artery revascularization significantly improved wound healing in patients with CLI. Endovascular revascularization is effective to facilitate healing of wounds in CLI and can be performed without significant complications.